2014
DOI: 10.12973/eurasia.2014.1115a
|View full text |Cite
|
Sign up to set email alerts
|

How to Enlarge the Scope of the Curriculum Integration of Mathematics and Science (CIMAS): A Delphi Study

Abstract: Studies have not yet consented whether integrating mathematics into science would enhance students' learning or confuse their understanding of abstract mathematical concepts. In spite of the social need for solving social-scientific problems with multiple facets, there has not been a holistic integration model of the disciplines. Hence, this study aims to propose a theoretical model for curriculum integration of mathematics and science (CIMAS) and to examine experts' opinions about its educational perspectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The Gjoligaj panel (2015) was entirely located in Albania, but the researcher was in Brooklyn, New York. Kim and Aktan (2014) were located in Korea and Turkey, respectively. Researchers are no longer bounded by geography in recruiting participants or in addressing issues of international concern.…”
Section: Lack Of Geographical Limitationmentioning
confidence: 99%
“…The Gjoligaj panel (2015) was entirely located in Albania, but the researcher was in Brooklyn, New York. Kim and Aktan (2014) were located in Korea and Turkey, respectively. Researchers are no longer bounded by geography in recruiting participants or in addressing issues of international concern.…”
Section: Lack Of Geographical Limitationmentioning
confidence: 99%
“…Alongside the subject of integration of mathematics and natural sciences is widely studied in the literature. For example, Kim and Aktan (2014) showed that all units in the mathematics curriculum in Turkey can be integrated with physics, chemistry or biology. This integration will promote both motivation for learning and social needs.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…diSessa (1993) states that concepts are not to be considered alone in terms of the epistemological position in constructivism and they are linked with other concepts. In order to promote meaningful learning and change concepts in students' mind, there should be ecology of the concept without thinking the concept alone (Duit & Treagust, 2003;Furner & Kumar, 2007;Kim & Aktan, 2014). Similarly, Novak (2011) suggested that the CI is necessary for the meaningful learning.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%